2006
DOI: 10.1080/03009740600844498
|View full text |Cite
|
Sign up to set email alerts
|

Hormone replacement therapy may prevent the development of isolated pulmonary hypertension in patients with systemic sclerosis and limited cutaneous involvement

Abstract: HRT administration may be effective in SSc post-menopausal women, preventing the development of iPHT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
44
1
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 11 publications
1
44
1
4
Order By: Relevance
“…Future studies are needed to investigate the possible correlation between plasma estrogen levels, pulmonary levels of ERb and ERa, and the severity of PH in these women. The fact that (1) postmenopausal women have an increased risk for the development of pulmonary hypertension (46), and that (2) hormone replacement therapy may prevent the development of PH in these patients further supports the beneficial role of E2 in patients with PH (47). Other investigators have also suggested that severe PH has now become overwhelmingly a disease of postmenopausal women (48).…”
Section: The Estrogen Paradox In Phmentioning
confidence: 77%
“…Future studies are needed to investigate the possible correlation between plasma estrogen levels, pulmonary levels of ERb and ERa, and the severity of PH in these women. The fact that (1) postmenopausal women have an increased risk for the development of pulmonary hypertension (46), and that (2) hormone replacement therapy may prevent the development of PH in these patients further supports the beneficial role of E2 in patients with PH (47). Other investigators have also suggested that severe PH has now become overwhelmingly a disease of postmenopausal women (48).…”
Section: The Estrogen Paradox In Phmentioning
confidence: 77%
“…These factors include the several effects of estrogens on their different receptors and opposite effects (especially on cell proliferation) exerted by several peripheral estrogen metabolites. Although the loss of reproductive hormones associated with postmenopausal status may be a risk factor for both PAH (4,42,51) and CAD (6,13,23,55), it is unclear to what extent the increase in both risks after reaching menopause represents hormonal changes vs. simply advancing age. It may in the end be that regulated, physiological estrogen production by the body is useful but that we can't recapitulate that with exogenous estrogen.…”
mentioning
confidence: 99%
“…17 This postmenopausal increase is also demonstrated in PAH and is postulated to be due to estrogen withdrawal, as it has been demonstrated in animal models that lower estrogen and progesterone states produce increased pulmonary vasoconstriction. 17,[21][22][23][24] Despite the known effects of estrogen on the pulmonary vasculature, it remains unclear how menopause affects response to treatment of PAH in general, including with phosphodiesterase type 5 (PDE-5) inhibitors. A treatment agent with a postmenopausal-specific treatment benefit would be extremely valuable given the high prev-alence of PAH in this population compared with that in men and younger women.…”
mentioning
confidence: 99%